THE DEVELOPMENT OF E-LEARNING SYSTEM ON LANGUAGE LEARNING FOR ENGLISH DEPARTEMENT STUDENT OF TEACHER TRAINING AND EDUCATION FACULTY OF SYIAH KUALA UNIVERSITY - Khairul Umam (Jurnal Peluang, 2015)
AbstractThe development of education toward e-learning is an alternative to improve the quality of education as e-learning uses internet technology in learning activity with a wide range access. There are three criteria that lies on the principle of education develoment toward e-learning model according to (Rosenberg, 2001): (1) e-learning is a network with the ability to renew, to store, to distribute, and to share learning material or information, (2) the transfering of information to the user through computer using a standard internet technology, (3) focusing on the broadest view concerning learning behind the traditional learning paradigm. E-learning research on distance education, is a concept that has changed teaching and learning method in higher education institutions in Indonesia that was conducted by (Darmayanti et al, 2007). The implementation of e-learning in “Universitas Terbuka” toward online tutorial that combined with web-based supplement or web-supplemen. The research shows that learning is not ought to be done in certain time and place. But learning process can be done anytime and anywhere by utilizingng internet in e-Learning model, which is a learning that free bound to space and time, accessible anytime and anywhere. The research gives result that e-Learning can improve the effectiveness of students’ learning, expand the coverage, and improve the quality of teaching and learnigKeyword: e-learning system, language learning